2019
DOI: 10.1186/s12889-019-6610-y
|View full text |Cite
|
Sign up to set email alerts
|

Personal ultraviolet Radiation exposure in a cohort of Chinese mother and child pairs: the Chinese families and children study

Abstract: Background Few studies in China have examined personal ultraviolet radiation (UVR) exposure using polysulfone dosimetry. Methods In this study, 93 mother and adolescent child pairs ( N = 186) from two locations in China, one rural (higher latitude) and one urban (lower latitude), completed 3 days of personal UVR dosimetry and a sun/clothing diary, as part of a larger pilot study. Results The average daily ambient UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Such detailed analyses of urban and rural differences and inclusion of cross-generational comparisons are important because of rapid increases in sedentary behavior, obesity, diabetes, and urban–rural disparities in China [ 41 ]. The results reported here and in related papers concerning UVR exposure, diet and other variables [ 29 , 30 , 31 ] also provide valuable guidance both for a potential follow up to the 1993–1995 Community Intervention Program (CIP) and for PA measurement in other cohort studies in China. Additionally, high response rates and largely complete data reflect the investment on standardized training of interviewers and ongoing data quality monitoring during data collection.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Such detailed analyses of urban and rural differences and inclusion of cross-generational comparisons are important because of rapid increases in sedentary behavior, obesity, diabetes, and urban–rural disparities in China [ 41 ]. The results reported here and in related papers concerning UVR exposure, diet and other variables [ 29 , 30 , 31 ] also provide valuable guidance both for a potential follow up to the 1993–1995 Community Intervention Program (CIP) and for PA measurement in other cohort studies in China. Additionally, high response rates and largely complete data reflect the investment on standardized training of interviewers and ongoing data quality monitoring during data collection.…”
Section: Discussionmentioning
confidence: 65%
“…Two urban male offspring were missing step counts. Further details concerning these dyads are available [ 30 , 31 ]. Briefly, over all respondents, mean age of mothers was 38.7 (Range 35–54) and offspring 15.1 (Range 14–17) years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, a study of 623 individuals from northern China found differences between men and women in their knowledge, awareness, and behaviour towards sun protection, where the women scored significantly higher in these areas ( P = 0.0001), while 16.4% of men reported not using sun protection methods [ 19 ]. In line with this, a survey of 5964 individuals in Shanghai found that over 70% of men did not wear hats or long pants and long-sleeved shirts to avoid the sun, 88% never used umbrellas, and 97% never used sunscreen [ 27 , 28 ], while Kimlin et al [ 29 ] found that men in China experience notably greater UV exposure due to extensive outdoor activities and little sun protection.…”
Section: Discussionmentioning
confidence: 95%